Can student English competence be measured by using standardized test?: A reflection of previous English examination on assessment policy - Alfian Alfian (Jurnal Bahtera: Jurnal Pendidikan, Bahasa, Sastra, dan Budaya, 2023)
Assessment is one the important aspect in education process. However, the assessment that relies on the examination, especially written test cannot describe the student real competence in English especially for speaking skill. This paper presents the reflection of previous policy in the assessment in English subject. This paper argues that there are discrepancy of the assessment practice and assessment theory which is implemented by the ministry of education. In addition, this paper also suggests several methods of assessment in English and provide the principles of language assessment and its implementation in the examination, finally this paper also recommended to accommodate school-based and external assessments.